Fireproof coating for underground flame suppression and directional crystallization strengthening and preparation method thereof

By introducing LBL-modified ZIF-67, mullite powder, and hollow alumina spheres into the downhole fire retardant coating, a dense columnar crystal layer is formed, which solves the problems of easy loosening and insufficient flame extinguishing ability of existing coatings at high temperatures. It achieves efficient flame extinguishing and structural strengthening, ensuring the integrity and rapid response of the coating in high-temperature environments.

CN121495415AActive Publication Date: 2026-02-10CHINA UNIV OF MINING & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511881515.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-02-10
Estimated Expiration
2045-12-15

Smart Images

  • Figure CN121495415A_ABST
    Figure CN121495415A_ABST
Patent Text Reader

Abstract

The invention discloses a fire retardant coating for underground flame suppression and directional crystallization strengthening and a preparation method of the fire retardant coating, and belongs to the technical field of coating compositions. Comprising the following raw materials: a water-based acrylic emulsion, LBL modified ZIF-67, mullite powder, hollow alumina balls, silica sol, ethylene glycol monoethyl ether acetate, a sodium polycarboxylate dispersing agent, a polyether modified organic silicon defoaming agent and deionized water. According to the underground flame suppression and oriented crystallization reinforced fireproof coating and the preparation method thereof, the waterborne acrylic emulsion is used as a film forming base material, the LBL modified ZIF-67 is used as a flame suppression core, and the mullite powder and the hollow alumina balls are used as oriented crystallization phases; the functions of efficient film-forming adhesion, active adsorption flame suppression and directional structure strengthening are synchronously realized, and the film-forming property of the water-based emulsion, the methane adsorption and flame suppression properties of the modified ZIF-67 and the mechanical and high-temperature stability of a crystal phase are synergistically exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating composition technology, and in particular to a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement, and its preparation method. Background Technology

[0002] Currently, underground fire-retardant coatings are mainly divided into two categories: water-based acrylic and silicate. Commercially available water-based acrylic coatings use acrylic emulsion as a base, relying on the heat-insulating layer formed after film formation to achieve fire resistance. Due to their good flowability, they are widely used for spraying on tunnel walls and equipment exteriors. Silicate coatings use sodium silicate and potassium silicate as bases, exhibiting excellent high-temperature resistance, withstanding temperatures exceeding 600℃. They are often used for protecting high-temperature equipment such as transfer conveyors and crushers. Neither type of coating incorporates active flame retardancy or structural reinforcement design.

[0003] Existing coatings lack active flame-retardant components and rely solely on coating thickness to delay heat transfer. They cannot adsorb combustible media such as methane and coal dust in mines, nor can they inhibit the chain reaction of combustion free radicals. Their response to rapidly spreading flames is significantly delayed. Water-based acrylic coatings have low mechanical strength, while silicate coatings are brittle and prone to cracking at high temperatures. Furthermore, they lack a crystalline strengthening structure, making the coating prone to loosening at high temperatures. Damaged coatings require recoating and cannot be repaired or reinforced independently, leading to interruption of protection. They can only achieve "one-time heat insulation protection" without a secondary reinforcement mechanism. Summary of the Invention

[0004] The purpose of this invention is to provide a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement, and its preparation method. The coating uses an aqueous acrylic emulsion as the film-forming base, LBL-modified ZIF-67 as the flame-suppressing core, and mullite powder + hollow alumina spheres as the directional crystalline phase. Through the synergistic compatibility of each component, it simultaneously achieves efficient film formation and adhesion, active adsorption and flame suppression, and directional structural reinforcement functions. It synergistically leverages the film-forming properties of the aqueous emulsion, the methane adsorption and flame-suppressing properties of the modified ZIF-67, and the mechanical and high-temperature stability of the crystalline phase.

[0005] To achieve the above objectives, the present invention provides a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement, comprising the following raw materials by weight: 25-35 parts of water-based acrylic emulsion, 8-12 parts of LBL-modified ZIF-67, 5-8 parts of mullite powder, 3-5 parts of hollow alumina spheres, 4-6 parts of silica sol, 2-4 parts of ethylene glycol ethyl ether acetate, 0.5-1 part of sodium polycarboxylate dispersant, 0.3-0.6 parts of polyether-modified silicone defoamer, and 30-40 parts of deionized water.

[0006] This invention also provides a method for preparing the above-mentioned downhole flame-retardant and directionally crystallized reinforced fireproof coating, comprising the following steps: S1. Preparation of LBL modified ZIF-67: ZIF-67 is first pretreated, then modified to obtain modified ZIF-67, and the modified ZIF-67 is dried to obtain LBL modified ZIF-67. S2. Preparation of film-forming base material: First, prepare the base material, and then add additives to the base material to obtain a uniform and transparent film-forming base material; S3. Preparation of fire-retardant coating: The LBL-modified ZIF-67 obtained in S1 and the film-forming base material obtained in S2 are mixed, ground and stirred to obtain the fire-retardant coating.

[0007] Preferably, the specific operation of S1 is as follows: S11, ZIF-67 pretreatment: Place ZIF-67 in a vacuum drying oven and dry it under normal pressure to remove surface adsorbed water; S12, ZIF-67 modification: Add the dried ZIF-67 from S11 to an aqueous solution of polyallylamine hydrochloride, stir, soak, filter, wash, then add an aqueous solution of ammonium dihydrogen phosphate, and repeat the stirring, soaking, filtering, and washing to obtain modified ZIF-67. S13, Drying of modified ZIF-67: The product obtained in S12 was placed in a vacuum drying oven and dried to obtain LBL modified ZIF-67.

[0008] Preferably, in S11, the temperature in the vacuum drying oven is 80-85℃, and the drying time is 4-5 hours; In S12, the mass percentage of the polyallylamine hydrochloride aqueous solution is 1-3 wt%, and the amount used is 10-15 times the mass of the pretreated ZIF-67 obtained in S11. The stirring rate is 300-400 rpm, the soaking time is 30-40 min, the filtration is carried out using a Buchner funnel, and the solution is washed 3-5 times with deionized water. The mass percentage of the ammonium dihydrogen phosphate aqueous solution is 1-3 wt%, and the amount used is 12-13 times the mass of the pretreated ZIF-67 obtained in S11. In S13, the temperature in the vacuum drying oven is 60-80℃, and the drying time is 2-3 hours.

[0009] Preferably, in S12, polyallylamine hydrochloride aqueous solution and ammonium dihydrogen phosphate aqueous solution are used for alternating soaking, and the mixture is filtered and washed after each soaking, with the alternating soaking being repeated 3 times.

[0010] Furthermore, in S12, the amount of polyallylamine hydrochloride aqueous solution is 10-15 times the mass of the pretreated ZIF-67 obtained in S11, or 80-180 parts by mass, and the amount of ammonium dihydrogen phosphate aqueous solution is 12-13 times the mass of the pretreated ZIF-67 obtained in S11, or 96-156 parts by mass.

[0011] Preferably, the specific operation of S2 is as follows: S21. Preparation of base material: Add aqueous acrylic emulsion to deionized water and stir until there are no obvious particles in the system to obtain the base material; S22. Preparation of film-forming base material: Ethylene glycol ethyl ether acetate, sodium polycarboxylate dispersant, and polyether-modified silicone defoamer are added sequentially to the base material obtained in S21, and stirred to obtain a uniform and transparent film-forming base material.

[0012] Preferably, in S21, the aqueous acrylic emulsion is added at a rate of 5-7 mL / min, and the mixture is stirred for 10-15 min. In S22, the rate of addition of ethylene glycol ethyl ether acetate is 2-3 mL / min, the rate of addition of sodium polycarboxylate dispersant is 1-2 mL / min, and the rate of addition of polyether modified silicone defoamer is 0.5-1 mL / min. The stirring time for each addition is 5-10 min, and the temperature throughout the process is 25-30℃.

[0013] Furthermore, the ethylene glycol ethyl ether acetate has a purity of ≥99.5% and a boiling point of 156℃; the sodium polycarboxylate dispersant has a solid content of 40%-45% and a molecular weight of 2000-3000; and the polyether-modified silicone defoamer has a solid content of 30%-35% and a viscosity of 500-800 mPa·s.

[0014] Preferably, the specific operation of S3 is as follows: S31. Material dispersion: Add LBL modified ZIF-67 to the film-forming base material, stir, add mullite powder and hollow alumina balls, and stir to obtain a mixed system; S32. Grinding and screening: Transfer the mixed system obtained in S31 into a sand mill for grinding and screening; S33, Crystallization control: At room temperature, add silica sol to the system after grinding and screening of S32, stir, and obtain flame retardant coating.

[0015] Preferably, in S31, the addition rate of LBL modified ZIF-67 is 1-2 g / min, the stirring speed is 1000-1200 rpm, and the stirring time is 10-15 min; the addition rate of mullite powder is 2-3 g / min, the stirring speed is 1000-1200 rpm, and the stirring time is 10-15 min; the addition rate of hollow alumina balls is 1-2 g / min, the stirring speed is 1000-1200 rpm, and the stirring time is 10-15 min. In S32, the grinding speed is 2000-2500 rpm, the grinding time is 10-15 min, the outlet temperature of the sand mill is ≤40℃, and the material with a screening particle size is ≤4μm; In S33, the silica sol is added at a rate of 1-2 mL / min, the stirring speed is 900-1000 rpm, and the stirring time is 10-15 min.

[0016] Furthermore, the purity of the mullite powder is ≥99% and the particle size is 5-10μm, while the purity of the hollow alumina spheres is ≥95%, the particle size is 20-30μm, and the porosity is 60%-70%.

[0017] Furthermore, the prepared fire-retardant coating is suitable for the protection of underground tunnel walls and equipment surfaces.

[0018] Therefore, the present invention employs the above-mentioned fire-retardant coating for downhole flame suppression and directional crystallization reinforcement, and its preparation method, which has the following beneficial effects: (1) Using waterborne acrylic emulsion as film-forming base material, LBL modified ZIF-67 as flame extinguishing core, and mullite powder + hollow alumina spheres as directional crystalline phase, the functions of "efficient film formation and adhesion - active adsorption and flame extinguishing - directional structural strengthening" are realized simultaneously through the synergistic compatibility of each component, and the film-forming properties of waterborne emulsion, the methane adsorption and flame extinguishing properties of modified ZIF-67, and the mechanical and high-temperature stability of crystalline phase are synergistically utilized. (2) The LBL interlayer assembly technology was creatively applied to the modification of ZIF-67. Instead of ordinary modification treatment, 2wt% polyallylamine hydrochloride aqueous solution and 2wt% ammonium dihydrogen phosphate aqueous solution were alternately soaked (3 cycles) to form functional groups on the surface of the modified ZIF-67. While maintaining the nanoscale particle size, it also has methane adsorption and flame propagation suppression, which is significantly better than unmodified ZIF-67 or products treated with a single modifier. (3) A unique “flame-extinguishing core-directional crystalline phase” interlocking reinforcement structure was formed. Through the induction effect of silica sol and sand milling, mullite powder and hollow alumina spheres were directionally grown into a dense columnar crystal layer during the coating film formation process. This crystal layer and LBL modified ZIF-67 are interlocked in three-dimensional space, which does not affect the flame-extinguishing adsorption function of ZIF-67, and at the same time ensures that the integrity is ≥90% under a single combustion and explosion test; (4) A controllable segmented preparation process was adopted. By precisely controlling the addition rate of each component, stirring speed and temperature, the coating system was ensured to be uniformly dispersed without agglomeration and to remain undivided after standing for 24 hours.

[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0020] Figure 1 This is a comparison chart of methane adsorption and coating peeling in Example 1 and Comparative Examples 1-2 of the present invention, which describes a fire-retardant coating for downhole flame suppression and directional crystallization enhancement and its preparation method. Figure 2 This is a comparison diagram of flame propagation distance between Example 1 and Comparative Examples 1-2 of the present invention, which describes a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement and its preparation method. Detailed Implementation

[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0022] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0023] Example 1 This invention provides a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement, the preparation method of which includes the following steps: S1. Preparation of LBL-modified ZIF-67: ZIF-67 is first pretreated, then modified to obtain modified ZIF-67, and the modified ZIF-67 is dried to obtain LBL-modified ZIF-67. The specific operation is as follows: S11, ZIF-67 pretreatment: Place 10 parts of raw ZIF-67 in a vacuum drying oven and dry at 82℃ under normal pressure for 4.5 hours to remove surface adsorbed water; S12, ZIF-67 modification: Add dried ZIF-67 to 80 parts of 2wt% room temperature polyallylamine hydrochloride aqueous solution, stir at 350 rpm for 35 min, filter with a Buchner funnel, and wash three times with deionized water; then add it to 96 parts of 2wt% room temperature ammonium dihydrogen phosphate aqueous solution, stir at 350 rpm for 35 min, and repeat the filtration and washing operations; the above process is repeated three times. S13. Drying of modified ZIF-67: The ZIF-67 after final washing is placed in a vacuum drying oven and dried at 70℃ for 2.5h to obtain LBL modified ZIF-67 flame extinguishing filler.

[0024] S2. Preparation of film-forming base material: First, prepare the base material, then add additives to the base material to obtain a uniform and transparent film-forming base material. The specific operation is as follows: S21. Preparation of base material: Slowly add 30 parts of aqueous acrylic emulsion to 36.7 parts of deionized water at a rate of 6 mL / min, stir for 10 min until there are no obvious particles in the system; S22. Preparation of film-forming base material: Add 3 parts of ethylene glycol ethyl ether acetate at a rate of 2.5 mL / min, 0.8 parts of sodium polycarboxylate dispersant at a rate of 1.5 mL / min, and 0.5 parts of polyether modified silicone defoamer at a rate of 0.8 mL / min in sequence. The stirring time for each addition is 5 min, and the temperature is maintained at 28℃ throughout the process to obtain a transparent and uniform film-forming base material.

[0025] S3. Preparation of fire-retardant coating: The LBL-modified ZIF-67 obtained in S1 and the film-forming base material obtained in S2 are mixed, ground, and stirred to obtain the fire-retardant coating. The specific operation is as follows: S31. Material dispersion: At room temperature, add 10 parts of LBL modified ZIF-67 to the film-forming base material at a rate of 1.5 g / min and stir for 10 min; add 6 parts of mullite powder at a rate of 2.5 g / min, and then add 4 parts of hollow alumina balls at a rate of 1.5 g / min. After each addition, stir at a stirring rate of 1100 rpm for 10 min. S32. Grinding and screening: Transfer the above mixture into a sand mill, set the grinding speed to 2200 rpm and grind for 10 minutes, while ensuring that the outlet temperature is ≤40℃. After grinding, screen the material with a particle size ≤4μm. S33. Crystallization control: At room temperature, add 5 parts of silica sol to the ground system at a rate of 1.5 mL / min, stir at a stirring rate of 900 rpm for 10 min to obtain the finished coating. The finished coating should stand for 24 h without any layering.

[0026] Example 2 The only difference between this embodiment and Example 1 is that in Example 2, 25 parts of aqueous acrylic emulsion are added in S21, and 2 parts of ethylene glycol ethyl ether acetate, 0.5 parts of sodium polycarboxylate dispersant, and 0.3 parts of polyether modified silicone defoamer are added in S22. All other conditions are the same.

[0027] Example 3 The only difference between this embodiment and Example 1 is that in Example 3, 35 parts of aqueous acrylic emulsion are added in S21, and 24 parts of ethylene glycol ethyl ether acetate, 1 part of sodium polycarboxylate dispersant, and 0.6 parts of polyether modified silicone defoamer are added in S22. All other conditions are the same.

[0028] Example 4 The only difference between this embodiment and embodiment 1 is that in embodiment 4, 12 parts of LBL modified ZIF-67, 8 parts of mullite powder, and 5 parts of hollow alumina spheres are added in S31, and 6 parts of silica sol are added in S33. All other conditions are the same.

[0029] Example 5 The only difference between this embodiment and embodiment 1 is that in embodiment 5, 8 parts of LBL-modified ZIF-67, 8 parts of mullite powder, and 5 parts of hollow alumina spheres are added in S31, and 4 parts of silica sol are added in S33. All other conditions are the same.

[0030] Comparative Example 1 The only difference between this comparative example and Example 1 is that LBL-modified ZIF-67 was not added to the raw materials of Comparative Example 1. By mass, it includes the following raw materials: 30 parts of water-based acrylic emulsion; 6 parts of mullite powder + 4 parts of hollow alumina balls; 5 parts of silica sol; 3 parts of ethylene glycol ethyl ether acetate; 0.8 parts of sodium polycarboxylate dispersant; 0.5 parts of polyether-modified silicone defoamer; and 46.7 parts of deionized water.

[0031] The preparation process does not include the preparation of LBL-modified ZIF-67, and LBL-modified ZIF-67 is not added in S3; all other conditions are the same.

[0032] Comparative Example 2 The only difference between this comparative example and Example 1 is that the raw materials of Comparative Example 2 did not contain mullite powder and hollow alumina balls. By mass, it includes the following raw materials: 30 parts of water-based acrylic emulsion; 10 parts of LBL-modified ZIF-67; 5 parts of silica sol; 3 parts of ethylene glycol ethyl ether acetate; 0.8 parts of sodium polycarboxylate dispersant; 0.5 parts of polyether-modified silicone defoamer; and 46.7 parts of deionized water.

[0033] In the preparation process, no mullite powder or hollow alumina spheres are added in S3, and all other conditions are the same.

[0034] The products prepared in Example 1 and Comparative Examples 1-2 were coated onto several 200mm×200mm×3mm 304 stainless steel test plates at 35°C and 75% relative humidity, and the film formation time was recorded.

[0035] The coated test plate was fixed to the inner wall of a 1500mm×250mm×250mm experimental pipe and at the 1500mm end of the pipe. A 9.5% methane-air mixture was introduced to a pressure of 0.1MPa. Simultaneously, a high-speed camera was activated, the igniter was triggered, and the entire process of the flame propagating from the ignition end to the end of the combustion section was recorded.

[0036] After the explosion, immediately turn on the nitrogen inlet switch, record the methane gas composition at the outlet, remove the test plate, and observe and calculate the coating peeling situation.

[0037] The results are as follows Figure 1 and Figure 2 As shown, LBL-modified ZIF-67 introduces flame-retardant groups through ammonium dihydrogen phosphate modification, increasing methane adsorption capacity and significantly reducing the flame propagation speed of the methane-air mixture, with a flame extinguishing response time of <0.1s.

[0038] Depend on Figure 1It can be seen that silica sol induces the directional growth of mullite powder and hollow alumina spheres, forming a dense columnar crystal layer, which improves the integrity of the coating at high temperatures. Example 1 showed the best performance, with the lowest coating peeling rate, significantly better than Comparative Examples 1-2.

[0039] Example 1 showed the lowest drop rate (approximately 0.1), while Examples 2-5 showed drop rates between 0.1 and 0.3, all maintaining a low level. This indicates that the formulation of the present invention achieves high integrity of the coating at high temperatures (integrity ≥90% in a single combustion and explosion test) through the synergistic effect of the "flame-extinguishing core-directional crystalline phase".

[0040] The drop rate of Comparative Example 2 was higher than that of Example 1, indicating that although LBL-modified ZIF-67 can play a flame-extinguishing role, it lacks the support of a dense columnar crystal layer formed by directional crystallization. The coating is easy to loosen and fall off at high temperature, which verifies the necessity of synergistic strengthening of flame-extinguishing core and directional crystallization phase.

[0041] The drop rate of Comparative Example 1 was higher than that of Example 1, indicating that relying solely on the directional crystalline phase (mullite powder + hollow alumina spheres) cannot fully guarantee the coating adhesion stability at high temperatures. The interlocking structure between the flame extinguishing core and the crystalline phase is crucial to the integrity of the protective layer.

[0042] Example 1 uses silica sol to induce the directional growth of mullite powder and hollow alumina spheres to form a dense columnar crystal layer, which is interlocked with LBL-modified ZIF-67 in three-dimensional space. This retains the function of the flame extinguishing core and improves the mechanical strength and high-temperature stability of the coating through the crystal structure. Therefore, it has the lowest peeling rate under combustion and explosion impact and high temperature environment. In contrast, Comparative Example 1 lacks a flame extinguishing core and the crystal phase lacks interlocking support. Comparative Example 2 lacks a crystal phase and the coating structure is loose, both of which lead to a higher peeling rate.

[0043] Depend on Figure 2 As can be seen from the relationship between distance (mm) and arrival time in the figure, the flame of Example 1 takes significantly longer to reach the same distance than that of Comparative Example 1 and Comparative Example 2, and may not reach the test endpoint of 1000mm or 1500mm, indicating that its flame extinguishing response speed is fast (<0.1s) and can effectively suppress the rapid spread of flame.

[0044] Example 1 has the smallest curve slope, and the time it takes for the flame to reach the same distance is significantly longer than other samples. Moreover, it does not reach the 1500mm endpoint within the test range (or the arrival time is much longer than the control sample), indicating that its flame extinguishing response speed is the fastest (<0.1s), and it can effectively suppress the rapid spread of flame.

[0045] The curve trends of Examples 2-5 are consistent with those of Example 1, except that the arrival time is slightly shorter than that of Example 1. This indicates that slight adjustments to the proportions of each component in the formulation (such as changes in the amount of waterborne acrylic emulsion and LBL-modified ZIF-67) have an impact on the flame extinguishing effect, but the overall flame suppression capability remains excellent.

[0046] Comparative Example 1 showed the fastest flame propagation speed. Due to the lack of methane adsorption and free radical inhibition effects of LBL-modified ZIF-67, the heat insulation coating alone could not stop the flame spread, thus verifying the key role of active flame extinguishing in the protective response.

[0047] The flame propagation speed of Comparative Example 2 was faster than that of Example 1 but slower than that of Comparative Example 1, indicating that LBL-modified ZIF-67 can adsorb methane and inhibit the combustion free radical chain reaction through the flame-retardant groups introduced by ammonium dihydrogen phosphate, thus exerting a flame-extinguishing effect. However, the absence of the directional crystalline phase does not affect the function of the flame-extinguishing core, but only affects the coating durability.

[0048] LBL-modified ZIF-67, through LBL interlayer assembly technology, alternately soaks in polyallylamine hydrochloride and ammonium dihydrogen phosphate aqueous solution (3 cycles). The functional groups formed on the surface significantly increase the methane adsorption capacity, while inhibiting the combustion free radical chain reaction, thus significantly reducing the flame propagation speed. In contrast, Comparative Example 1, lacking this flame-extinguishing core, relies solely on the heat insulation coating to delay heat transfer, failing to prevent the combustion of flammable media and flame spread, resulting in the fastest flame propagation speed.

[0049] Figure 1 The improvement in coating durability due to directional crystallization has been verified. Figure 2 The flame-extinguishing core was verified to suppress flame propagation, which together supported the ingenuity of the film-forming base material-flame-extinguishing core-directional crystallization phase synergistic system, proving that the solution simultaneously solves the two major defects of existing coatings: lack of flame extinguishing ability and easy failure of protective layer.

[0050] Therefore, this invention employs the above-mentioned downhole flame-retardant and directional crystallization-enhanced fireproof coating and its preparation method, using water-based acrylic emulsion as the film-forming base material, LBL-modified ZIF-67 as the flame-retardant core, and mullite powder + hollow alumina spheres as the directional crystallization phase. Through the synergistic compatibility of each component, it simultaneously achieves efficient film-forming adhesion, active adsorption flame retardation, and directional structural enhancement functions, synergistically leveraging the film-forming properties of the water-based emulsion, the methane adsorption and flame retardation properties of the modified ZIF-67, and the mechanical and high-temperature stability of the crystalline phase.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A fire-retardant coating for downhole flame suppression and directional crystallization reinforcement, characterized in that: By weight, it includes the following raw materials: 25-35 parts water-based acrylic emulsion, 8-12 parts LBL modified ZIF-67, 5-8 parts mullite powder, 3-5 parts hollow alumina spheres, 4-6 parts silica sol, 2-4 parts ethylene glycol ethyl ether acetate, 0.5-1 part sodium polycarboxylate dispersant, 0.3-0.6 parts polyether modified silicone defoamer, and 30-40 parts deionized water.

2. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement as described in claim 1, characterized in that: Includes the following steps: S1. Preparation of LBL modified ZIF-67: ZIF-67 is first pretreated, then modified to obtain modified ZIF-67, and the modified ZIF-67 is dried to obtain LBL modified ZIF-67. S2. Preparation of film-forming base material: First, prepare the base material, and then add additives to the base material to obtain a uniform and transparent film-forming base material; S3. Preparation of fire-retardant coating: The LBL-modified ZIF-67 obtained in S1 and the film-forming base material obtained in S2 are mixed, ground and stirred to obtain the fire-retardant coating.

3. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement according to claim 2, characterized in that: The specific operation of S1 is as follows: S11, ZIF-67 pretreatment: Place ZIF-67 in a vacuum drying oven and dry it under normal pressure to remove surface adsorbed water; S12, ZIF-67 modification: Add the dried ZIF-67 from S11 to an aqueous solution of polyallylamine hydrochloride, stir, soak, filter, wash, then add an aqueous solution of ammonium dihydrogen phosphate, and repeat the stirring, soaking, filtering, and washing to obtain modified ZIF-67. S13, Drying of modified ZIF-67: The product obtained in S12 was placed in a vacuum drying oven and dried to obtain LBL modified ZIF-67.

4. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement according to claim 3, characterized in that: In S11, the temperature in the vacuum drying oven is 80-85℃, and the drying time is 4-5 hours; In S12, the mass percentage of the polyallylamine hydrochloride aqueous solution is 1-3 wt%, and the amount used is 10-15 times the mass of the pretreated ZIF-67 obtained in S11. The stirring rate is 300-400 rpm, the soaking time is 30-40 min, the filtration is carried out using a Buchner funnel, and the solution is washed 3-5 times with deionized water. The mass percentage of the ammonium dihydrogen phosphate aqueous solution is 1-3 wt%, and the amount used is 12-13 times the mass of the pretreated ZIF-67 obtained in S11. In S13, the temperature in the vacuum drying oven is 60-80℃, and the drying time is 2-3 hours.

5. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement according to claim 3, characterized in that: In S12, polyallylamine hydrochloride aqueous solution and ammonium dihydrogen phosphate aqueous solution are soaked alternately, and filtered and washed after each soaking, and the alternating soaking is repeated 3 times.

6. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement according to claim 2, characterized in that: The specific operation of S2 is as follows: S21. Preparation of base material: Add aqueous acrylic emulsion to deionized water and stir until there are no obvious particles in the system to obtain the base material; S22. Preparation of film-forming base material: Ethylene glycol ethyl ether acetate, sodium polycarboxylate dispersant, and polyether-modified silicone defoamer are added sequentially to the base material obtained in S21, and stirred to obtain a uniform and transparent film-forming base material.

7. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement according to claim 6, characterized in that: In S21, the aqueous acrylic emulsion is added at a rate of 5-7 mL / min, and stirred for 10-15 min. In S22, the rate of addition of ethylene glycol ethyl ether acetate is 2-3 mL / min, the rate of addition of sodium polycarboxylate dispersant is 1-2 mL / min, and the rate of addition of polyether modified silicone defoamer is 0.5-1 mL / min. The stirring time for each addition is 5-10 min, and the temperature throughout the process is 25-30℃.

8. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement according to claim 2, characterized in that: The specific operation of S3 is as follows: S31. Material dispersion: Add LBL modified ZIF-67 to the film-forming base material, stir, add mullite powder and hollow alumina balls, and stir to obtain a mixed system; S32. Grinding and screening: Transfer the mixed system obtained in S31 into a sand mill for grinding and screening; S33, Crystallization control: At room temperature, silica sol is added to the system after grinding and screening of S32, and stirred to obtain flame-retardant coating.

9. The method for preparing a fire-retardant coating for downhole flame suppression and directional crystallization reinforcement according to claim 8, characterized in that: In S31, the addition rate of LBL modified ZIF-67 is 1-2 g / min, the stirring speed is 1000-1200 rpm, and the stirring time is 10-15 min; the addition rate of mullite powder is 2-3 g / min, the stirring speed is 1000-1200 rpm, and the stirring time is 10-15 min; the addition rate of hollow alumina balls is 1-2 g / min, the stirring speed is 1000-1200 rpm, and the stirring time is 10-15 min. In S32, the grinding speed is 2000-2500 rpm, the grinding time is 10-15 min, the outlet temperature of the sand mill is ≤40℃, and the material with a screening particle size is ≤4μm; In S33, the silica sol is added at a rate of 1-2 mL / min, the stirring speed is 900-1000 rpm, and the stirring time is 10-15 min.

Citation Information

Patent Citations

  • Reflective thermal-insulation exterior wall coating

    CN103555102A

  • In-situ synthesis mullite whisker-toughened ceramic heat accumulator and preparation method thereof

    CN103804007A

  • High-infrared-reflection heat-insulation coating for exterior wall building and preparation method thereof

    CN103881484A

  • High-temperature-resistant nanometer hole heat-preserving paint and preparation method thereof

    CN104152029A

  • Antifogging coating, method of producing the same, method of forming antifogging coating film and formed product having antifogging coating film

    JP2003082272A